Application of The Primum Remedium Principle in Corruption Crime Cases - Esa Arung Syuhada; Nanda Dwi Rizkia; Susilawati Susilawati; Dika Kurnia Edo Kisworo; Artina Wahyu Dwi Nugrahaeni (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This research believes that the application of the Primum Remidium principle in Corruption Crimes in Indonesia can achieve its goal, namely eradicating corruption more easily. The researcher's beliefs will be accompanied by scientific arguments and using a systematic research methodology. This research is qualitative research with a descriptive approach, namely describing the urgency of implementing the Primum Remidium principle in criminal acts of corruption in Indonesia. The data that researchers use in this article is primary data obtained from credible sources in the form of scientific articles, books, websites, and other things. These data were analyzed using the stages of data collection, data analysis, data reduction, and drawing conclusions. The reult in this article show The application of the Primum Remidium principle in criminal acts of corruption must be applied to 8 types of criminal acts of corruption which include state finances, bribery, embezzlement, extortion, fraudulent acts, conflicts of interest, and gratification. In these 8 types of corruption, there should no longer be any such thing as mediation, the principle of presumption of innocence, mediation, and so on which are forms of the ultimum remidium principle. If the investigator has met the qualifications for evidence, then the potential corruptors should be processed immediately without compromising the quality of the evidence